Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together (Nht) terhadap Keaktifan Siswa dalam Proses Pembelajaran PAI - Muhamad Ripin Ikwandi (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
This research is motivated by the still many learning processes in schools that position students as listeners to teacher lectures. As a result the learning process tends to be boring and makes students passive in learning. Therefore, it is necessary to find the right learning formula, so that it can increase student activity in the learning process, namely by implementing the Numbered Heads Together type of cooperative learning model. Cooperative learning type NHT which is divided into several small groups with 2-6 students per group. Each student is numbered 1-6 or more and the teacher randomly calls one number. The objectives of this study are: 1) To find out the implementation of the NHT type of cooperative learning model in the PAI learning process, 2) To determine student learning activeness, 3) And to determine whether there is an effect of NHT type cooperative learning model on student learning activeness. This type of research is a kind of correlational quantitative research where the analysis uses statistics and in this case the data obtained through several techniques include observation, interviews, questionnaires, and documentation. The data obtained to answer the above problems are 1) that the implementation of the NHT cooperative learning model in the PAI learning process is classified as good with a value of 79%, 2) that the learning activeness of students in the PAI learning process is classified as good with an 81% process. While the presence or absence of the influence of the NHT cooperative learning model on student learning activeness in the PAI learning process is evidenced by the results of the product moment formula which is 0.830 consulted with the interpretation of the